Association of Baseline Smoking Status with Long-Term Prognosis in Patients Who Underwent Percutaneous Coronary Intervention: Large Single-Center Data - Ru Liu; Zhan Gao; Huanhuan Wang; Xiaofang Tang; Lijian Gao; Ying Song; Jingjing Xu; Jue Chen; Shubin Qiao; Yuejin Yang; Runlin Gao; Bo Xu; et al. (Journal of Interventional Cardiology)
Objectives. This study analyzed a large sample to explain the association of baseline smoking state with long-term prognosis of coronary artery disease (CAD) patients who underwent percutaneous coronary intervention (PCI). Background. Data is limited up to now regarding whether smoker’s paradox exists in Chinese population. Methods. A total of 10724 consecutive cases were enrolled from January to December 2013. 2-year clinical outcomes were evaluated among current smokers and nonsmokers. Major adverse coronary event (MACCE) included all-cause death, revascularization, myocardial infarction (MI), and stroke. Results. Current smokers and nonsmokers accounted for 57.1% and 42.9%, respectively. Current smokers were presented with predominant male sex, lower age, and less comorbidities. The rates of 2-year all-cause death were not significantly different among two groups. But the rate of stroke and bleeding was significantly higher in nonsmokers than in current smokers (1.6% and 1.1%, P=0.031; 7.2% and 6.1%, P=0.019). The rate of revascularization was significantly higher in current smokers than in nonsmokers (9.1% and 8.0%, P=0.037). Multivariable Cox regression indicated that, compared with nonsmokers, current smokers were not independently associated with all endpoints (all P>0.05). Conclusions. 2-year all-cause death, MACCE, MI, revascularization, stroke, ST, and bleeding risk were similar between current smokers and nonsmokers in CAD patients undergoing PCI.